Peran Pemerintah Desa dalam Meningkatkan Partisipasi Masyarakat untuk Membayar Pajak Bumi dan Bangunan di Desa Pringgasela - M. Saleh; Sarkawi; H. A. Khair (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
Land and Building Tax (PBB) is one of the regional revenue sources that plays an important role in supporting regional development, including development at the village level. Community participation in paying Land and Building Tax is strongly influenced by the role of village governments in providing socialization, education, and administrative assistance to the community. However, in practice, several challenges are still found in increasing public awareness to fulfill tax obligations, particularly at the village level. This community service activity aims to improve public understanding of the importance of paying Land and Building Tax and encourage community participation in fulfilling tax obligations. The implementation method used a participatory approach through counseling, Focus Group Discussion (FGD), and administrative consultation. The activity was conducted on July 15, 2025, at the Village Office Hall of Pringgasela with consisting of village officials, community leaders, and community representatives. The results showed that public understanding regarding the importance of paying Land and Building Tax improved after the activity. In addition, this activity identified several obstacles faced by the community in fulfilling tax obligations, such as limited understanding of payment procedures and low legal awareness. This activity contributes to increasing community participation in Land and Building Tax payments and supports regional revenue improvement.